Odpowiedź :
3.
a)
2x + 17x = 26 - x
2x + x = 26 - 17
3x = 9 /:3
x = 3
b)
11 - x = 3x + 8
-x - 3x = 8 - 11
-4x = -3 /:(-4)
x = 3/4
c)
-7(x + 2) + 4 = -3x
-7x - 14 + 4 = -3x
-7x+3x -10 = 9
-4x = 10 /:(-4)
x = -10/4
x = -2¹/₂
Odpowiedź:
a) 2x+17 = 26-x
2x +x= 26-17
3x= 9 /: 3
x=3
spr... 2*3 + 17= 26-3
6+17= 23
23 = 23
L=P
b) 11 - x = 3x +8
-x - 3x = 8 -11
-4x = -3 /:( -4)
x= 3/4
spr... 11 - 3/4 = 3*3/4 +8
10 i 4/4- 3/4= 9/4 +8
10 i 1/4 = 2 i 1/4 +8
10 i 1/4 = 10 i 1/4
L=P
c) - 7 ( x+2) +4 = - 3x
-7x -14 +4= - 3x
- 7x + 3x = 14-4
-4x = 10 /: (-4)
x= - 10/4 = -2 i 1/2
spr... - 7 *(-10/4) -14 +4 = - 3 * (-10/4)
70/4 - 14+4= 30/4
17 i 2/4 - 14 +4= 7 i 2/4
21 i 2/4 - 14= 7 i 1/2
7 i 1/2= 7 i 1/2
L=P
Szczegółowe wyjaśnienie: